Current and future impacts of drought and ozone stress on Northern Hemisphere forests. (22nd September 2020) - Otu‐Larbi, Frederick; Conte, Adriano; Fares, Silvano; Wild, Oliver; Ashworth, Kirsti
Abstract: Rising ozone (O3 ) concentrations, coupled with an increase in drought frequency due to climate change, pose a threat to plant growth and productivity which could negatively affect carbon sequestration capacity of Northern Hemisphere (NH) forests. Using long‐term observations of O3 mixing ratios and soil water content (SWC), we implemented empirical drought and O3 stress parameterizations in a coupled stomatal conductance–photosynthesis model to assess their impacts on plant gas exchange at three FLUXNET sites: Castelporziano, Blodgett and Hyytiälä. Model performance was evaluated by comparing model estimates of gross primary productivity (GPP) and latent heat fluxes (LE) against present‐day observations. CMIP5 GCM model output data were then used to investigate the potential impact of the two stressors on forests by the middle (2041–2050) and end (2091–2100) of the 21st century. We found drought stress was the more significant as it reduced model overestimation of GPP and LE by 11%–25% compared to 1%–11% from O3 stress. However, the best model fit to observations at all the study sites was obtained with O3 and drought stress combined, such that the two stressors counteract the impact of each other. With the inclusion of drought and O3 stress, GPP at CPZ, BLO and HYY is projected to increase by 7%, 5% and 8%, respectively, by mid‐century and by 14%, 11% and 14% by 2091–2100 as atmospheric CO2 increases. Estimates were up to 21% and 4% higher when drought and O3 stress were neglected respectively. Drought stress will have a substantial impact on plant gas exchange and productivity, off‐setting and possibly negating CO2 fertilization gains in future, suggesting projected increases in the frequency and severity of droughts in the NH will play a significant role in forest productivity and carbon budgets in future. Abstract : Plant growth and productivity of Northern Hemisphere (NH) forests are hindered by rising ozone (O3 ) concentrations and increasing drought frequency and severity. We used a vegetation model to study the relative contributions of drought and O3 stress to changes in plant productivity and gas exchange at selected NH forests, and how these contributions change in future under a business‐as‐usual climate scenario. Drought stress was found to be more significant for plant gas exchange than O3 in both present‐day and future climate scenarios. However, the combination of drought and O3 stress provided the best model‐observation fit at all sites.